2010
DOI: 10.1182/blood-2009-08-237727
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 study of lumiliximab combined with fludarabine, cyclophosphamide, and rituximab in patients with relapsed or refractory chronic lymphocytic leukemia

Abstract: Preclinical data demonstrate enhanced antitumor effect when lumiliximab, an anti-CD23 monoclonal antibody, is combined with fludarabine or rituximab. Clinical data from a phase 1 trial with lumiliximab demonstrated an acceptable toxicity profile in patients with relapsed or refractory chronic lymphocytic leukemia (CLL). We therefore pursued a phase 1/2 dose-escalation study of lumiliximab added to fludarabine, cyclophosphamide, and rituximab (FCR) in previously treated CLL patients. Thirty-one patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…Compared to a historic cohort treated with FCR [12], the CR rate was twice as high (52 % vs. 25 %). The toxicity was comparable [21].…”
Section: Lumiliximabmentioning
confidence: 85%
“…Compared to a historic cohort treated with FCR [12], the CR rate was twice as high (52 % vs. 25 %). The toxicity was comparable [21].…”
Section: Lumiliximabmentioning
confidence: 85%
“…The humanized anti-CD23 has been developed and used in clinical trials [16]. A phase I/II clinical trial showed that the addition of anti-CD23 to fludarabine, cyclophosphamide, and rituximab (FCR) in previously treated CLL/SLL patients resulted in a higher complete response rate, and did not appear to enhance toxicity, indicating that anti-CD23 synergistically enhances antitumor activity of FCR [17]. The investigation of the relation between the levels of CD23 expression and clinical response may be beneficial to achieve the best therapeutic effect without inadvertent addition of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] This is also the case for CD19, a glycoprotein member of the Ig superfamily, 69 and HLA-DR, a class II antigen of the major histocompatibility complex. 70 In a Phase I/II study, 91 patients with relapsed/ refractory NHL, CLL, and multiple myeloma were enrolled to receive MEDI-551, an antibody targeting CD19.…”
Section: Other Moabsmentioning
confidence: 93%